The Role of Urban Sustainability in Placemaking: Measuring the Urban Dimension - Al-Issawi, Zahraa Mohammed; Al-Jumaily, Saad Khudhair (International Journal of Environment, Engineering & Education, 2021)
The research sheds light on the importance of the role that urban sustainability plays in placemaking, where the research discussed the principle of including sustainability at the urban level in its comprehensive concept, which includes the economic, environmental, and social dimensions in the placemaking process to reach sustainable models of urban places that are environmentally friendly and inexpensive or consuming energy sources. Renewable and more appropriate to the cultures and values of the local community, and the researchers emphasized that reaching an urban place-based on sustainability will contribute significantly to adapting to the problems of climate change, the shortage of energy sources and its high cost, reduces environmental pollution problems, increases the efficiency of the use of spaces and meets the different needs of its users. The primary research data were obtained for the selected samples (Salhia Residential Complex and Al Salam Residential Complex) using a questionnaire as a tool consisting of a set of questions directed to 20 people who were identified according to the experience and objectives of the study And coming out with the conclusions of the practical study that showed that the process of a sustainable urban placemaking is a dynamic process and that by its nature it supports continuity and compatibility with the environment, However, there are complementary principles, foundations, and goals that have been added from a sustainable perspective to reach urban spaces that are more compatible and responsive to the current challenges.